Semantic and Structural Peculiarities of Adjectival Comparative Constructions of Superiority in Modern Literary Lithuanian - Janulienė, Aušra (Kalbotyra, 1987)
An attempt is made to describe the semantic and structural peculiarities of Lithuanian comparative constructions of superiority. Special attention is paid to the presuppositional properties and usage peculiarities of the constructions.